Behaviour of a social unit of sperm whales (Physeter macrocephalus) entangled in a driftnet off Capo Palinuro (Southern Tyrrhenian Sea, Italy) - Pace, D. S.; Miragliuolo, A.; Mussi, B. (J. Cetacean Res. Manage., 2023)
Driftnet fishing is notorious for being the major source of fatal entanglement of cetaceans and for its devastating impact on some pelagic species of the Mediterranean fauna. Of all the large cetaceans, the sperm whale (Physeter macrocephalus) is most affected by this fishing technique. On 9 August 2004, a group of five sperm whales, two adult females and three juvenile individuals, was found trapped in a driftnet 40 miles southwest off Capo Palinuro (Italy). Their tails were totally immobilised by the net and one animal was completely entangled. All the animals showed numerous lesions on their bodies. The group was freed by the Italian Coast Guard scuba-diving team during a two-day rescue operation. This exceptional case of sperm whale disentanglement was a unique opportunity to study the group’s acoustic and general behaviour during a particularly stressful event. Out of a total video/acoustic recording of 110 minutes, 91 were examined. During the rescue procedures, the whales’ behaviour was described as open mouthed, sideways roll, agitation of fluke and pectoral fins, head rubbing, fluke contact (with head, flippers and back by the liberated animals) and defecation. As expected, the entangled individuals produced different patterns of clicks, identified as ‘usual clicks’, ‘codas’ and ‘creaks’. Each pattern was associated with specific behaviour. Despite international and national regulation banning fishing with driftnets in the Mediterranean Sea, driftnets continue to be used illegally in this sperm whale habitat, posing a constant threat to the species’ survival in the region.